Differences in Flexible and Rigid Bronchoscopy for Assessment of Tracheomalacia. (13th April 2020) - Hysinger, Erik B.; Hart, Catherine K.; Burg, Gregory; De Alarcon, Alessandro; Benscoter, Dan
Abstract : Objectives/Hypothesis: Both flexible and rigid bronchoscopy can be used to assess tracheomalacia; however, there is limited evidence comparing the two techniques. The objective of this study was to compare flexible and rigid bronchoscopy for evaluating the location and severity of tracheomalacia in children. Study Design: Retrospective case series. Methods: This was a retrospective study of children with both flexible and rigid bronchoscopy under the same sedation. All bronchoscopies were reviewed by three bronchoscopists for the location and severity of tracheomalacia. The location of collapse was defined as upper, middle, or lower trachea, and the severity of collapse was defined as none (0%–25% collapse), mild/moderate (26%–75% collapse), and severe (>75% collapse). Results: Twenty‐one patients were recruited for this study with a variety of neonatal respiratory diseases. There was 94% agreement (κ = 0.64) for assessment of tracheomalacia in the upper trachea. However, agreement was only 75% (κ = 0.50) in the middle trachea and 76% (κ = 0.52) in the lower trachea. In the subset of patients without tracheostomy, agreement improved to 100%, 88%, and 82% for the upper, middle, and lower trachea, respectively. There was poor correlation for tracheomalacia severity in the middle trachea (ρ = 0.30, P = .2) and moderate in the lower trachea (ρ = 0.63, P = .002). Conclusions: Although there is moderate agreement between flexible and rigid bronchoscopy for evaluating the presence of tracheomalacia, there can be differences in the two techniques, particularly when assessing severity of airway collapse. Future studies will be needed to understand factors that result in the discordance of flexible and rigid bronchoscopy for assessing airway dynamics. Level of Evidence: 4 Laryngoscope, 131:201–204, 2021